2016
DOI: 10.1149/2.0161611jes
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Gap Alkaline Water Electrolysis Using Ion-Solvating Polymer Electrolyte Membranes at Reduced KOH Concentrations

Abstract: Membranes based on poly(2,2 -(m-phenylene)-5,5-bibenzimidazole) (m-PBI) can dissolve large amounts of aqueous KOH to give electrolyte systems with ion conductivity in a practically useful range. The conductivity of the membrane strongly depends on the concentration of the aqueous KOH phase, reaching about 10 −1 S cm −1 or higher in 15-25 wt% KOH. Herein, m-PBI membranes are systematically characterized with respect to performance and short-term stability as electrolyte in a zero-gap alkaline water electrolyzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 57 publications
3
78
0
5
Order By: Relevance
“…In previous work, it was shown that the conductivity of KOH doped mPBI peaks at KOH concentrations of about 20-25%. [19,20,27,28]. After doping at 25wt% it reached about 0.1 S cm -1 [25], which was confirmed in the present work (Figure 6a).…”
Section: Mechanical Propertiessupporting
confidence: 89%
See 2 more Smart Citations
“…In previous work, it was shown that the conductivity of KOH doped mPBI peaks at KOH concentrations of about 20-25%. [19,20,27,28]. After doping at 25wt% it reached about 0.1 S cm -1 [25], which was confirmed in the present work (Figure 6a).…”
Section: Mechanical Propertiessupporting
confidence: 89%
“…This electrolyte system has been extensively evaluated for hydrogen [19] and direct alcohol [22][23][24] fuel cells. Recently, membranes of various polybenzimidazole chemistries [25][26][27][28][29] and polybenzimidazole-based polymer blend membranes [30] have been investigated as separator in alkaline water electrolysis. The reported data indicate reduced ohmic losses in the higher current density range, which clearly 4 demonstrate the feasibility of the concept.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KOH/m-PBI system was first described by Xing and Savadogo 15 in 2000 for fuel cell applications, and we conducted the first demonstration for water electrolysis in 2013. 16 The membranes achieve the highest specific conductivity when equilibrated in bulk electrolyte concentrations in the range of 20-25 wt% KOH 17 and exhibit remarkable, though not complete stability, for up to six months in concentrated KOH. 18 They do, however, in contrast to AEMs, show negligible conductivity in KOH concentrations below 5 wt%.…”
mentioning
confidence: 99%
“…When a concentration of 20-25 wt % aqueous KOH is analysed the best results are obtained. With 5,15, and 30 wt % the operation of the electrolyser is stable but its subsequent analysis evidenced oxidative degradation of m-PBI in 15 and 30 wt % KOH [16].…”
Section: Introductionmentioning
confidence: 99%